An Echocardiographic Study of Right Ventricular Morphology and Function in Systemic Hypertension. - Barakoti, Murari Prasad; Karki, Adhyashree; Chaulagain, Manoj Kumar; Karki, D B (Nepalese Heart Journal, 2021)
Background and Aims: Hypertension is a common medical condition that leads to increased risk of cardiovascular conditions including coronary artery disease, heart failure, stroke, renal diseases, blindness and cardiovascular death. Long term hypertension will affect left ventricle by hypertrophy and several functional derangements. Since heart works as a unit, right heart changes are expected. Right ventricular dysfunction has a strong prognostic significance and we aim to study right ventricular parameters in hypertensive patients. Methods: We studied 71 hypertensive subjects and 66 matched control without hypertension in echocardiography laboratory for chamber dimensions and right ventricular systolic and diastolic parameters. Results: The right ventricular free wall thickness (5.46±1.97mm vs 4.77±0.81mm; P=0.01) and interventricular septal thickness (11.62±2.64mm vs 9.10±1.16mm; P<0.01) were significantly higher among hypertensive patients. Right ventricular dimensions namely basal diameter (26.41±4.97mm vs 29.16±5.22mm; P<0.01), mid-ventricular diameter (25.83±4.40mmvs 27.44±5.05mm; P=0.05) and right ventricular long-axis length (69.54±7.08 mm vs 73.28±7.08mm; P<0.01) were significantly low among hypertensive patients. Tricuspid Annular Plane Systolic Excursion (TAPSE) was significantly lower among hypertensive patients (18.84±1.85mm vs control 20.54±2.65mm; P<0.01). A significant statistical correlation was found between mitral E/A ratio and tricuspid E/A ratio (R2 linear=0.78, P=0.01). Conclusion: The effect of hypertension in right ventricular structure and function are found to be subtle but definite as seen in diastolic wave velocities, right ventricular wall thickness, internal chamber dimensions and TAPSE. Assessment of hypertensive effect on heart will help to control hypertension in stringent way.